(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
High-resolution paleolimnological studies based on multi-proxy analysis constitute an important tool to reconstruct the evolution of aquatic systems as well as evaluating their responses to natural and/or anthropogenic forcing factors (Lotter, 2003; Birks and Birks, 2006). While individual palaeoecological studies reveal local developments, general patterns often only emerge when information from several sites is combined together. Numerous shallow lakes occur throughout the Pampa plain of Argentina, between 33° to 39°S and 57° to 66°W. These lakes present two alternative states of equilibrium (Sche- ffer and Jeppesen, 2007; Scheffer and van Ness, 2007). Some of them are turbid lakes due to the high amount of algae, while others are clear macrophyte- dominated lakes. A third type of lake that can be recognized within the region is inorganic-turbid lakes, in which turbidity is caused by high amount of suspended inorganic material (Quirós et al., 2002; Allende et al., 2009). These lakes are characterized by low productivity, with scarce phytoplankton and macrophytes. Most of the lakes developed on defla- tion basins that originated during the late Pleistocene by the prevailing westerly winds. Often, the lakes are associated to lunettes, fixed palaeodunes that developed at the shore, on the windward side of the basins (Tricart, 1973; Zárate and Tripaldi, 2012). During the Holocene, the basins became areas of groundwater discharge and surface water accumu- lation gradually filling with sediments. Today, the lakes are nutrient-rich, eutrophic to hypereutrophic, and polymictic, too shallow to develop thermal stra- tification. Water depth and salinity are highly variable. During summer and/or during episodic droughts the lakes suffer significant reduction in water volume, and thus strong fluctuations in their water levels (Quirós and Drago, 1999; Sosnovsky and Quirós, 2006). These aquatic systems are able to support an abundance of macrophytes and phyto- plankton, which have proven to leave an exceptional fossil record of environmental changes (Stutz et al. 2002, 2006, 2010, 2012; Fontana, 2005). For more than a decade the authors have been investigating these aquatic systems in order to reconstruct their evolutionary history and the regional environments with the main goal of inferring the past climatic conditions. In order to achieve this, multi-proxy analysis of diverse biological indicators were carried out in several lakes of the south-east region of the Pampa plain. Pollen, non-pollen palynomorphs and plant macrofossil remains and associated fauna were analysed in sediment sequences from lake Hinojales- San Leoncio (37º23’S; 57º23’W) and lake Tobares (37°30’S; 57°28’W). These new results were then combined with former investigations from lakes Lonkoy (37º12’S; 57º25’W), Nahuel Rucá (37º37’S; 57º26’W) and Hinojales (37º34’S; 57º27’W) (Fig. 1). The studied lakes range in suface from 200 to 300 ha and a water depth of about 1 m. The regional vegeta- tion is characterized by temperate subhumid grass- lands, knowns as pampas. The modern landscape is strongly influenced by human activities since the establishment of European settlements in the XVI century. The land has been intensively used, in particular for grassing, as well as for agriculture. Native trees are absent in the vegetation, except for Celtis ehrenbergiana, a deciduous tree known as tala, which occurs on Pleistocene lunette dunes and Holocene ridges of shell debris. The aquatic plant communities of the studied sites are characterized by several species of emergent, free-floating leaved and submerged macrophytes. The lakes are surrounded by a ring of Schoenoplectus californicus, among which other emergent macrophytes occur: e.g. zizaniopsis bonariensis, typha latifolia, Hydro cotyle bonariensis, H. ranunculoides, alternanthera philloxeroides, Solanum glaucophyllum, Bacopa monnieri, Polygonum punctatum, ranunculus apiifo lius, triglochin striata, and Phyla canescens. Near the shore, in sheltered areas, free floating plants like ricciocarpus natans, azolla filiculoides, limnobium laevigatum, lemna valdiviana, Wolffia brasiliensis, Wolffiella lingulata and W. oblonga form a dense carpet. Diverse submerged macrophytes occur when the water tends to be clear, so the light available is enough for their development: e.g. Myriophyllum elatinoides, Ceratophyllum demersum, Potamogeton pectinatus, and zannichellia palustris together with diverse Charophytes. The studied sediment records were recovered with different samplers: Dacknovsky (Hinojales), vibracorer (Nahuel Rucá, Hinojales-SL and Tobares) and Livingston-type corer (Lonkoy). The chronology of the records is based on AMS radiocarbon age determinations on terrestrial plant remains, where possible (Table 1). Gastropod shells of Heleobia parchappii have also been used for dating, since previous studies have yielded reliable results (Fontana, 2005, 2007). Age-depth models (Fig. 2) are constructed using CLAM 2.2 (Blaauw, 2010) with the Southern Hemisphere calibration curve, SHCal13 (Hogg et al., 2013). The studied records, spanning the time since the middle Holocene, document similar evolutionary pattern. Changes in the different proxies are consistent, showing similar trends in the evolution of the aquatic ecosystems (Figs. 3-7). At the beginning of the records a clear phase characterized the water bodies, dominated by the green algae Chara, the dinoflagellate Peridinium and aquatic plants such as Myriophyllum, ruppia and/or Potamogeton. At ca. 2,000 cal yr BP the diversity of submerged macro- phyte communities increased, indicating clear water lakes with increasing nutrient content. Towards ca. 700-500 cal yr BP the lakes switched to a turbid phase dominated by phytoplankton together with water fleas and flatworms. Among the phytoplankton the main constitutes are: Pediastrum, Scenedesmus and tetraedron species of green algae Desmidiaceae and the cyanobacterium Gloeotrichia. On land, halophyte plant communities, dominated by Cheno- podiaceae, surrounded the water bodies during the first clear-water phase, suggesting instable periods with brackish conditions. Towards the present, the surroundings of the lakes are characterized by dominance of Cyperaceae together with Bacopa, ranunculus, Polygonum, typha and apiaceae. This vegetation is characteristic of more stable environ- mental conditions. During the middle Holocene and part of the late Holocene, brackish-shallow lakes with clear water phases characterised the landscape of the south-east pampean plain. After ca. 2,000 cal. yr BP, water run-off and/or wind action increased, incorporating organic matter from the surroundings into the basins and initiating a gradual change towards the next phase. This dynamics could be associated to periods of pronounced drought followed by floods. A marked seasonality in the annual precipitation regimen would explain this dynamics indicating a regionally instable environ- ment with dryer climatic conditions than present (Zárate et al., 1998; Zárate, 2005; Vilanova et al., 2010; Laprida et al., 2014). The change to turbid conditions at around 700-500 cal yr BP was probably caused by a significant input of nutrients into the basin, impeding the development of submerged aquatic plants, characteristic of the clear phase, which in turn favoured the expansion of phyto- plankton. However, the presence of submerged macrophytes that tolerate some degree of turbidity like Miryophyllum, Ceratophyllum and Potamogeton would suggest that during some periods the level of turbidity did not reach critical values. The presence of submerged flowering plants may also suggest alternate periods of clear phases within a general turbid state. The synchronous change to a turbid face in all studied sites suggests a climatic regional trigger like an increase of precipitation, with a more stable seasonal regime. Similar values of precipitation compared to today did not occur until historical times (Irurzun et al., 2014; Laprida et al., 2014). This study constitutes the first of its type basing the reconstruction of paleoenvironmental and paleocli- matic conditions on the dynamics and functioning of the shallow lakes, studied in the context of multi- proxy and multi-site analysis.